Playful Pedagogy for German Speaking Skills: A Case Study on Game Integration in University Language Courses - Nursalam Nursalam; Nurming Saleh; Agung Rinaldy Malik (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Developing speaking skills remains a persistent challenge in foreign language education, often limited by students’ anxiety and low engagement. This study investigates how integrating playful pedagogy through structured game-based activities can enhance German speaking proficiency in a university context. Employing a qualitative case study approach, the research involved 20 intermediate-level German language students at a public university. Data were collected through classroom observations, student reflection journals, and structured interviews. Various games, including digital quizzes, role-playing scenarios, storytelling dice, and collaborative speaking tasks, were implemented progressively over one semester. The results show a significant increase in active participation, with speaking turns per student tripling compared to conventional sessions. Interview responses revealed high agreement that games reduced speaking anxiety (M = 4.76) and boosted confidence (M = 4.59), while observational data indicated improved utterance length and syntactic complexity. Despite these benefits, challenges such as limited time, dominant speakers in competitive settings, and occasional technical issues were noted. The study concludes that carefully designed game-based activities create a supportive, low-anxiety environment that encourages spontaneous language production and peer interaction. To maximize pedagogical impact, instructors should balance competitive and cooperative games, provide clear instructions, and allocate sufficient time for debriefing. These findings offer practical insights for enhancing communicative competence in German language courses at the university level through playful pedagogy.